The Simulation of Access Control List (ACLs) Network Security for Frame Relay Network at PT. KAI Palembang - Kurniati, Kurniati; Dasmen, Rahmat Novrianda (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi, 2019)
PT. KAI Palembang is a branch of PT. Kereta Api Indonesia (KAI) Persero located in South Sumatra Province, where PT. KAI Persero is an Indonesian State-Owned Enterprise that organizes railway transportation which provide services including passenger and goods transportation. PT. KAI Palembang has a computer network connected to PT. KAI Persero central is located in Jakarta. Now, PT. KAI Palembang is trying to improve computer network security, where one of them is limiting the access of users who connected to PT. KAI Palembang computer network. This can be done by implementing Access Control Lists (ACLs) and Frame Relay on PT. KAI Palembang computer network. In this research used the Network Development Life Cycle (NDLC) method which has several stages, namely Analysis, Design, Simulation Prototyping, Implementation, Monitoring and Management. This research method is used because the results of this research will be displayed in the Cisco packet tracer simulator. In addition, the results of this research were tested using a ping test between computers to show that the ACLs design had been running well.